Innovation intermediation in supply networks: Addressing shortfalls in buyer and supplier capabilities for collaborative innovation - Selviaridis, Kostas; Spring, Martin (Journal of Operations Management, 2025)
Abstract We investigate how innovation intermediaries address shortfalls in the capabilities that buyers and suppliers must have to access each other's knowledge for innovation purposes, also referred to as indirect capabilities. Prior research on supplier‐enabled innovation has identified various capabilities that buyers need in order to collaborate with innovative suppliers. It recognizes that suppliers also require capabilities to access buyer knowledge. However, we still know little about the role of innovation intermediaries—actors who are neither buyers nor suppliers, but still influence innovation processes and outcomes in supply networks. Our case‐based research shows that intermediaries create workspaces for R&D and experimentation, help to refine definitions of requirements and de‐risk novel solutions, support contracting, and facilitate solution implementation. We contribute to research on supplier innovation by developing a model of intermediaries' activities and underlying capabilities, and their impact on innovation sourcing outcomes. We elaborate the indirect capabilities theoretical perspective by introducing additional types of indirect capabilities for collaborative innovation in supply chains, and showing how these capabilities interrelate. We furthermore extend the literature on innovation intermediaries by elucidating hitherto unexplored capabilities for intermediation and adding insights regarding the contribution of intermediaries to open innovation processes.